A learning state?: a case study of the post-1994 South African welfare regime - Mungwashu, Sthembiso Handinawangu (Rhodes University, Faculty of Humanities, Department of Sociology, 2011)
This thesis examines the processes of policymaking in South Africa, as expressed through the shifts in income maintenance policy. The thesis focuses on the processes leading to the establishment of the South African Social Security Agency (SASSA), as its case study. SASSA is the institutional framework for the delivery of social grants. Our intention is to test the efficacy of what we have called 'state learning' in the South African context. Therefore, the overall aim of the study is to assess the capacity of the 'state to learn' in the process of policymaking as expressed through the shifts in social grant administration and the institutional framework of social welfare in South Africa. The subsidiary goals of the research includes mapping changes in the system of social grants administration since 1994 in order to assess the sources of the shifts in its institutional framework; to assess processes and responses within the state that result in policy shifts and the extent to which these can be considered dimensions of state learning; to assess the power of ideas in the policymaking process and to assess the influence of non-state agencies/actors in policy contestation and learning processes. This is essential, because social policy, especially welfare policy research in post-apartheid South Africa, has focused on the economic value of policies and not the political processes in policymaking. For the framework of analysis the study draws on theories of learning, especially at the organizational or institutional level. We start from the perspective that policymaking and implementation cannot be reduced to a neatly ordered schema (Lamb: 1987:6). Further, that policy change and policymaking are "iterative, haphazard, and highly political processes, in which the apparently logical sequences of decision-making, may turn out to be the reverse" (Lamb, 1987:6). This is mainly because state building is a complex affair and a contested terrain; policy learning and making are neither benign nor do they involve the state working in isolation (Sabatier, 1998). To understand processes of policymaking in South Africa, we rely on content analysis of primary and secondary materials or documents and in-depth interviews with key informants involved in the policy process. The documentary sources include records of parliamentary debates, green and white papers on social welfare, ANC party documents, presidential task force reports, newspapers, magazines and court judgments. The study reveals that the establishment of SASSA lends itself to the idea of 'state learning'. Learning is indicated in South Africa by the capacity and ability of the state to stimulate ideas, debate ideas to establish ideational matrixes as well as paradigms that have informed the development of policy, take ideas and implement them to try and solve mismatches between the intention of the state and the outcomes and the ability of the state to produce policy.
Keywords: South African Social Security Agency; South Africa -- Social policy; Poor -- South Africa; Social service -- South Africa; Public welfare -- South Africa; Social service -- Government policy -- South Africa